Adipose-Derived Stem Cells Accelerate Diabetic Wound Healing through the Induction of Autocrine and Paracrine Effects. Issue 1 (January 2016) - Kuo, Yur-Ren; Wang, Chun-Ting; Cheng, Jiin-Tsuey; Kao, Gour-Shenq; Chiang, Yuan-Cheng; Wang, Ching-Jen
Cell-based therapy is an attractive approach for the treatment of chronic nonhealing wounds. This study investigated whether adipose-derived stem cells (ASCs) can accelerate diabetic wound healing and traffic in the engraftment of ASCs. Dorsal full-thickness skin wound defects (6 × 5 cm) were created in a streptozotocin (STZ)-induced diabetes rodent model. Group I served as a nondiabetic normal control, group II served as a diabetic control without ASCs, and group III included rats that were injected subcutaneously in the wound margin twice with nondiabetic ASCs (1 × 10 7 ASCs/dose). The wound healing was assessed clinically. Histological examination and immunohistochemical analyses of periwound tissue were performed. Green fluorescence protein (GFP)+-ASCs were used to examine the engraftment of these cells after injection. XenoLight DiR-labeled ASCs were implanted to detect migration ability using an IVIS imaging system. Results revealed that complete wound healing time statistically decreased in the ASC-treated group compared to the controls (p < 0.001). Histological examination revealed the ASC-treated group showed a significant reduction in the proinflammatory reaction, with significantly increased levels of EGF, VEGF, rPH, and Ki-67 expression compared to the controls. The populations of GFP+-ASCs in circulating blood significantly increased after ASC injection compared to those of controls. Immunofluorescence staining showed GFP+-ASCs significantly accumulated in the subdermal layer of the wound margin and increased angiogenesis via vWF and VEGF expression after injection. IVIS analysis revealed ASCs could exist and home into the periwound area up to 8 weeks postimplantation. In conclusion, ASCs significantly enhanced diabetic wound healing, engrafted into the local wound tissue, and implanted into circulating blood. ASC treatment stimulated neoangiogenesis and increased tissue regeneration through paracrine and autocrine mechanisms.